2022
DOI: 10.1111/jam.15591
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore production in pseudomonas SP. strain SP3 enhances iron acquisition in apple rootstock

Abstract: Aims:The purpose of this study was to analyse the effects of siderophore-producing bacteria and bacterial siderophore on the iron nutrition of apple rootstocks under iron-deficient conditions. Methods and Results:We isolated three Pseudomonas strains, SP1, SP2 and SP3 from the rhizosphere of the Fe-efficient apple rootstocks using the chrome azurol S agar plate assay. We found that all three strains had the ability to secrete indole acetic acid-like compounds and siderophores, especially SP3. When Fe-inefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…External environmental factors also influenced the production of siderophore. Gao et al [ 45 ] purified the siderophorepyoverdine from Pseudomonas strain SP3, which reduced chlorosis caused by Fe deficiency in apple rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…External environmental factors also influenced the production of siderophore. Gao et al [ 45 ] purified the siderophorepyoverdine from Pseudomonas strain SP3, which reduced chlorosis caused by Fe deficiency in apple rootstocks.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the deepening of the research on siderophores, more and more attention has been paid to siderophores secreted by microorganisms (Table 4 shows that the data come from the WOS core database). Gao et al [56] and Ghavami et al [57] found that iron-secreting microorganisms can increase the iron content of plants, as well as promote the absorption of other elements such as zinc and phosphorus [58]. Siderophores exhibit natural biocontrol properties by inhibiting the growth and reproduction of pathogens through iron ion sequestration, effectively suppressing disease propagation.…”
Section: Functions Of Siderophores 251 Sustaining Normal Biological A...mentioning
confidence: 99%
“…These findings suggest that M. panacihumi has the potential to enhance the growth and health of P. ginseng and could be used to remediate heavy metal contamination in ginseng fields. In the study conducted by Gao et al [68], three Pseudomonas bacterial strains were evaluated, isolated from the rhizosphere of Fe-efficient apple rootstocks. Indole acetic acid-like substances and siderophores were found to be released by all three strains.…”
Section: Phytohormone Production For Reducing Fungicides and Pesticidesmentioning
confidence: 99%